(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Aim: To study the pattern of head injuries among patients admitted in a tertiary care hospital. Methods: A total of 194 consecutively admitted patients with history of head trauma were interviewed over a period of 6months as per semi-structured proforma. The demographic details of the patients including preliminary data, manner of sustaining injury, Computed Tomography (CT) findings, GCS (Glasgow Comma Scale) based severity of trauma and other relevant findings were recorded. Results: The study observed that young people with mean age of 36 years with an Inter Quartile Range (IQR) of 27, who fall in the age group of 21 to 40 years, were most commonly affected (49.5%). Road traffic Injuries (RTI 50.5%) was observed to be the most common manner of sustaining head injury. Males were affected in 86.6% of trauma cases and outnumbered females in RTI, falls and assaults. The head trauma in both genders was most commonly sustained in assaults (87%) and falls (24%) respectively. The study observed Extra-Axial Bleed-Subdural Haemorrhage (SDH) to be commonest finding followed by Intracranial Haemorrhage (ICH) whereas Subarachnoid